Copper-catalyzed 1, 4-alkylarylation of 1, 3-enynes with masked alkyl electrophiles. Issue 12 (25th February 2019) - Ye, Changqing; Li, Yajun; Zhu, Xiaotao; Hu, Shengmin; Yuan, Daqiang; Bao, Hongli
Abstract : A copper-catalyzed 1, 4-alkylarylation of 1, 3-enynes with alkyl diacyl peroxides as masked alkyl electrophiles and aryl boronic acids as nucleophiles, selectively affording structurally diversified tetrasubstituted allenes under mild conditions is reported. Abstract : Classical 1, 4-dicarbofunctionalization of 1, 3-enynes employs organometallic reagents as nucleophiles to initiate the reaction. We report a copper-catalyzed 1, 4-alkylarylation of 1, 3-enynes with alkyl diacyl peroxides as masked alkyl electrophiles and aryl boronic acids as nucleophiles, selectively affording structurally diversified tetrasubstituted allenes under mild conditions. Mechanistic studies suggest that an allenyl radical might be involved.